Untitled Pengaruh Sumber Polutan dalam Rumah dengan Kejadian ISPA di Kecamatan Bontoala - Suci Wulandhani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
Acute Respiratory Infections (ARI) are a major cause of mordibity and mortality in infectious diseases in the world. Environmentally based diseases are still the main cause of death in Indonesia. ARI disease in Indonesia is in the 10 list of the most common diseases in hospitals. In South Sulawesi Province, the number of patients with ARI in 2016 reached 117.467 cases and most of the patients were children. The occurrence of ARI is influenced by several factors, one of which is behavioral factors such as smoking habits, the use of fuel for cooking and the use of mosquito coils. Combustion smoke contains dust particles in which there are chemical elements that cause irritation and make breathing easy for infection. This study aims to determine the effect of indoor pollutant sources with the incidence of ARI. This study used a simple random sampling technique with a sample of 59 people. The result of statistical tests at the level of significance = 0.05 showed thet there was no significant effect between smoking habits (p value = 0.407) and the use of cooking fuel (p value = 0.833) with the incidence of ARI. There is an effect of using mosquito coils (p value = 0.05) with the incidence of ISPA disease in Bontoala District, Makassar. The use of mosquito coils is a risk factor for the incidence of ISPA because of the burning smoke of various particles that can cause irritation to the respiratory tract so that it can cause infection